14-3-3 epsilon is an intracellular component of TNFR2 receptor complex and its activation protects against osteoarthritis. Issue 12 (5th July 2021) - Fu, Wenyu; Hettinghouse, Aubryanna; Chen, Yujianan; Hu, Wenhuo; Ding, Xiang; Chen, Meng; Ding, Yuanjing; Mundra, Jyoti; Song, Wenhao; Liu, Ronghan; Yi, Young-Su; Attur, Mukundan; et al.
Abstract : Objectives: Osteoarthritis (OA) is the most common joint disease; however, the indeterminate nature of mechanisms by which OA develops has restrained advancement of therapeutic targets. TNF signalling has been implicated in the pathogenesis of OA. TNFR1 primarily mediates inflammation, whereas emerging evidences demonstrate that TNFR2 plays an anti-inflammatory and protective role in several diseases and conditions. This study aims to decipher TNFR2 signalling in chondrocytes and OA. Methods: Biochemical copurification and proteomics screen were performed to isolate the intracellular cofactors of TNFR2 complex. Bulk and single cell RNA-seq were employed to determine 14-3-3 epsilon (14-3-3ε) expression in human normal and OA cartilage. Transcription factor activity screen was used to isolate the transcription factors downstream of TNFR2/14-3-3ε. Various cell-based assays and genetically modified mice with naturally occurring and surgically induced OA were performed to examine the importance of this pathway in chondrocytes and OA. Results: Signalling molecule 14-3-3ε was identified as an intracellular component of TNFR2 complexes in chondrocytes in response to progranulin (PGRN), a growth factor known to protect against OA primarily through activating TNFR2. 14-3-3ε was downregulated in OA and its deficiency deteriorated OA. 14-3-3ε was required for PGRN regulation of chondrocyte metabolism. In addition, both global and chondrocyte-specific deletion of 14-3-3ε largely abolished PGRN's therapeutic effects against OA. Furthermore, PGRN/TNFR2/14-3-3ε signalled through activating extracellular signal-regulated kinase (ERK)-dependent Elk-1 while suppressing nuclear factor kappa B (NF-κB) in chondrocytes. Conclusions: This study identifies 14-3-3ε as an inducible component of TNFR2 receptor complex in response to PGRN in chondrocytes and presents a previously unrecognised TNFR2 pathway in the pathogenesis of OA.